Global cuisine Indian and Japanese [videorecording] (2012)
Celebrating the color, richness, and diversity of Indian and Japanese cuisines, this program investigates regional differences within each country, traditional and modern influences on contemporary cuisine, and the way in which certain foods are prepared, served, and eaten for everyday meals and special occasions. Interviews feature Indian writer Lakshmi Belekrishnan, Village Indian head chef Vissnu Kharel, Japanese language instructor Akiko Mahara, and Wabi Sabi owner and chef Tomoya Kawasaki. Geared toward both food technology and culture-related classes for young people, the video offers a great way to encourage international awareness and understanding-as well as suggestions for exciting culinary arts adventures!